2001
DOI: 10.1038/sj.ijo.0801642
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body weight change and cardiovascular disease risk factors in male former athletes

Abstract: OBJECTIVE:To evaluate the cardiovascular disease risk factor pro®le in former athletes according to their weight-change patterns during the postcompetitive period. DESIGN: Cohort study with a retrospective assessment of baseline weight of male former top-level athletes. SUBJECTS: One-hundred and ®fty top-level athletes aged 35 ± 60 y were divided into four groups according to the weightchange patterns during the postcompetitive period (weight loss, constant weight, weight gain over 3.0 kg and weight gain over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…11 On the other hand, overweight status and obesity were found to be significant contributors in the OxS and inflammation-based CVD risk profile among the former athletes. 11,18 However, it is not clear through which important atherogenic markers overweight can express increased CVD risk level in those who are physically active and have presumably high cardiorespiratory fitness. In the present study, ex-athletes were characterized by relatively high sports activity participation rate and this may improve the CVD risk profile independently of overweight status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 On the other hand, overweight status and obesity were found to be significant contributors in the OxS and inflammation-based CVD risk profile among the former athletes. 11,18 However, it is not clear through which important atherogenic markers overweight can express increased CVD risk level in those who are physically active and have presumably high cardiorespiratory fitness. In the present study, ex-athletes were characterized by relatively high sports activity participation rate and this may improve the CVD risk profile independently of overweight status.…”
Section: Discussionmentioning
confidence: 99%
“…18 The inclusion criteria for former athletes (n ¼ 60) were their previous participation in endurance sports events and sports games at the international or national level at least 15 years ago. The control group (n ¼ 54) consisted of age-matched male subjects of the ex-athletes who were currently physically inactive and had no competitive sports history.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In US nurses, long-term weight loss after age 18 was found to appreciably reduce the subsequent risk for hypertension. 5 Among male former athletes, Pihl and Jü rimäe 25 found that long-term weight loss (at least 15 years) was significantly associated with lower risk of hypertension. This is contradictory to the effect for short-term weight loss among the obese we found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…23 This might explain the observed associations between current BMI and CRP. Some studies 24 have reported that those who gained weight increased their waist-to-hip circumference ratio or abdominal fat mass and those who reduced weight decreased them. In vitro, human abdominal visceral adipose tissue releases more IL-6 compared to subcutaneous adipose tissue, 25 possibly explaining why the weight gain or loss (weight-slope) was independently associated with elevated CRP level after adjustment for current BMI and several confounders.…”
Section: Weight Fluctuation and Elevated Crpmentioning
confidence: 99%